Power Quality Improvement by Solar Photo-voltaic / Wind Energy Integrated System Using Unified Power Quality Conditioner - Sarita Samal; Prakash Kumar Hota (Institute of Advanced Engineering and Science, 2017)
The real problems in diminution of power quality occurs due to the rapid growth of nonlinear load are leads to sudden decrease of source voltage for a few seconds i.e sag, swell, harmonics in source and load current, voltage unbalance etc. All these problems can be compensated by using Unified Power Quality Controller (UPQC) and the operation of UPQC depends upon the available voltage across capacitor present in dc link. If the capacitor voltage is maintained constant then it gives satisfactory performance. The proposed research is basically on designing of Photo Voltaic (PV) /Wind energy fed to the dc link capacitor of UPQC so as to maintain proper voltage across it and operate the UPQC for power quality analysis. The said model is simulated in Matlab and results are verified by using FFT analysis.The proposed PV/ Wind energy-UPQC is design in Matlab simulation for reduction of voltage sag, swell, interruption of voltage, harmonics in load current and compensation of active and reactive power.